Metadata and universal access in digital library environments. Issue 2 (19th June 2017) - Beyene, Wondwossen Mulualem
Abstract : Purpose: Accessibility metadata has been a recurring theme in recent efforts aimed at promoting accessibility of information and communication technology solutions to all, regardless of their disabilities, cultural differences, language, etc. The purpose of this paper is to explore the potential of accessibility metadata in improving knowledge discovery and access in digital library environments, discuss developments in creating accessibility terms for resource description, and attempt to relate those developments to the overall purpose of universal design to finally recommend points for improvement. Design/methodology/approach: This is an exploratory study based on review of selected literature and documentations made available by metadata projects. Search for related literature was made using Google Scholar, EBSCO, and Web of Science Databases using terms and combination of terms such as "universal design and metadata, " "accessibility metadata, " "inclusive design, " and "metadata and digital libraries." Some documentation on metadata projects were obtained through e-mail correspondences. Findings: The overall discussion shows that accessibility metadata can be instrumental in exposing accessible resources to search engines and in augmenting library resource discovery tools for the benefit of users with disabilities. Accessibility metadata would help users to quickly discover materials that fit their needs. However, the notion of indexing resources by their accessibility attributes remains an area that needs further exploration. Originality/value: The paper gives emphasis to the importance of metadata research in universal design endeavors. It also provides recommendations for practical applications that would improve accessibility in digital library environments.